Tobacco Cessation and Tobacco Cessation Centre - Dr. Kalia Mehul (NMO Journal)
Tobacco is a small name but widely used addictive substance due to its easy availability, variable forms, and low cost. It not only affects mortality and morbidity caused by various non- communicable disease and cancer but also affect the global economy by increasing health cost and reducing effective earning hours & life expectancy. Government and NGOs have tried to reduce consumption by various modalities, but people haven't utilized facilities due to a lack of awareness, myths, and peer pressure. This articledescribes the tobacco cessation center's history, structure & function with the National Tobacco Control Programme, and penalties for violating the tobacco production act with the aim of increasing awareness of government facilities to prevent the consumption of various forms of tobacco.